2016
DOI: 10.1038/srep37977
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic modulation of RORγt translates to efficacy in preclinical and translational models of psoriasis and inflammatory arthritis

Abstract: The IL-23/IL-17 pathway is implicated in autoimmune diseases, particularly psoriasis, where biologics targeting IL-23 and IL-17 have shown significant clinical efficacy. Retinoid-related orphan nuclear receptor gamma t (RORγt) is required for Th17 differentiation and IL-17 production in adaptive and innate immune cells. We identified JNJ-54271074, a potent and highly-selective RORγt inverse agonist, which dose-dependently inhibited RORγt-driven transcription, decreased co-activator binding and promoted interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 70 publications
8
56
0
Order By: Relevance
“…Activation of CD4-depleted psoriatic co-cultures with SE or CA did not lead to the detectable production of IL-9, IL-17A, or IFN-g (see Supplementary Figure S4aec online). However, IL-17F, which is usually produced in higher amounts than IL-17A and is also known to be generated by the co-cultures (Xue et al, 2016), was detected in two of four experiments with SE (see Supplementary Figure S4d).…”
Section: Se-induced Il-9 Production By Circulating Cla D T Cells Requmentioning
confidence: 98%
“…Activation of CD4-depleted psoriatic co-cultures with SE or CA did not lead to the detectable production of IL-9, IL-17A, or IFN-g (see Supplementary Figure S4aec online). However, IL-17F, which is usually produced in higher amounts than IL-17A and is also known to be generated by the co-cultures (Xue et al, 2016), was detected in two of four experiments with SE (see Supplementary Figure S4d).…”
Section: Se-induced Il-9 Production By Circulating Cla D T Cells Requmentioning
confidence: 98%
“…This hypothesis seems to be confirmed by recent clinical trials for the treatment of chronic plaque psoriasis, in which the neutralizing anti‐IL23 monoclonal antibodies guselkumab, tildrakizumab or risankizumab have been tested and have demonstrated dramatic efficacy with a PASI90 response (90% or better response against the psoriasis area and severity index) achieved in up to 70 % of treated patients . In the literature, experimental mouse models using IL‐23 injections to induce psoriasis‐like phenotype have been described, and recently it has been reported this IL‐23‐induced skin inflammation was reduced in RORγt‐deficient mice and in wild‐type mice orally administered with a RORγ inverse agonist . An investigation was started to determine whether treatment with a RORγ inverse agonist applied topically on the skin was also able to dampen skin inflammation in this animal model.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, derivative 14 (CD12681; N‐ (2,4‐dimethylphenyl)‐ N ‐isobutyl‐2‐oxo‐1‐[(tetrahydro‐2 H ‐pyran‐4‐yl)methyl]‐2,3‐dihydro‐1 H ‐benzo[ d ]imidazole‐5‐sulfonamide) stood out as having the best balance of properties for topical application. Evaluated in an IL‐23‐induced skin inflammation model, 14 showed significant reduction in ear thickness and IL‐17 inflammatory cell recruitment . CD12681 is currently being evaluated in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…The orphan nuclear receptor gamma (RORγt) ligand-binding domain (Protein Data Bank ID, or PDB ID: 3B0W) was predicted to be the 3 rd top binding target for mometasone with a binding score of -10.4 (Figure 3a). Studies from the literature have found that IL-17 expressing cells and Th17-related signaling exist in acneiform lesions [35], and that RORγt is needed for Th17 cell differentiation and IL-17 production [36], [37]. Thus, it is possible that mometasone induces the occurrence of dermatitis acneiform by binding to RORγt and affecting the Th17/IL-17 level.…”
Section: Prediction and Possible Interpretation Of Mometasone-inducedmentioning
confidence: 99%